Analisis Kinerja Perangkat Desa Tutup Kecamatan Tunjungan Kabupaten Blora - Ratnawati, Dewi; Permana, Dian Fithra (Business and Accounting Education Journal, 2025)
This study aims to analyze the performance of village officials in Tutup Village, Tunjungan District, Blora Regency, in carrying out their main duties and functions, as well as to identify the factors contributing to their low performance, particularly in the context of information technology utilization. A descriptive qualitative approach was used, with data collected through observation, in-depth interviews, and documentation. The findings reveal that the performance of village officials remains suboptimal, characterized by low work discipline, limited understanding of duties, and insufficient competence in operating technology-based administrative systems. Only 60% of the officials are able to independently operate administrative applications, while the rest rely on their colleagues. The main factors affecting poor performance are a lack of skills and low work motivation. Limited mastery of information technology also hinders the achievement of efficient public services. This study recommends enhancing competence through information technology training and strengthening work motivation to support the development of professional and digitally adaptive village officials.